Topologies of tourism enclaves. Issue 5 (20th October 2019) - Ek, Richard; Tesfahuney, Mekonnen
Abstract: Research on tourism enclaves has relied mainly on topographical understandings of the phenomenon. The focus has been on the ontic, that which is or exists instead of the relational qualities or properties of tourism enclaves. Topographical conceptions thus tend to simplify enclavic processes and attributes that are much more complex than meets the eye. In this article, we make the case for topological understandings of tourism enclaves, based on a relational ontology, as a complement. We thereby strive to offer more nuanced conceptions of tourism enclaves. We depart from Agamben's political ontology to illustrate our claim. Seen topologically, tourism enclaves are not simply spaces marked-off from the norm, but rather constituents of the norm. Tourism enclaves need to be theorized as 'prototypes' or 'laboratories' of new subjectivities (ways of being, relating, and experiencing the world). The tourist thus emerges as a model figure of biopolitics in the contemporary, the norm rather than the exception. The tourist is not that which is abandoned by the sovereign in the manner of Agamben, but rather a free exilant, a subject that self-willingly chooses abandonment. We deploy topological concepts, like Agamben's the ban, the camp, and state of exception. Such a conception, we argue, widens the ontological register or horizon of tourism theory.